Application of Mobile Augmented Visual Reality (MAVR) for vocabulary learning in the ESL classroom - Jalaluddin, Ilyana; Darmi, Ramiza; Ismail, Lilliati (UiTM Press, 2021)
This repeated measure experiment study aimed to explore LINUS students or Low Achiever (LA) students’ improvement in learning English language vocabularies using Mobile Augmented Visual Reality (MAVR). It specifically tried to analyse the effect of MAVR on the English vocabulary development of 45 primary school students from the LINUS programme in Selangor. In this study, they were provided access to an AVR-game based apps in learning English vocabularies with mobile computing devices. Vocabulary size was later measured using the British Picture Vocabulary Scale II and analysed with repeated measures ANOVA. Analysis showed that there was an increase in the scores and the differences between the levels of the within-subjects factor was significant. This implies that Mobile Augmented Visual Reality (MAVR) materials can be used as an interactive tool for LA learners in learning a language. Findings highlight the role of teachers in the implementation process and point out possible directions for more effective application of MAVR in this field.